In vivo metabolic effects after acute activation of skeletal muscle Gs signaling - Jaroslawna Meister; Derek B.J. Bone; Jonas R. Knudsen; Luiz F. Barella; Liu Liu; Regina Lee; Oksana Gavrilova; Min Chen; Lee S. Weinstein; Maximilian Kleinert; Thomas E. Jensen; Jürgen Wess (Molecular Metabolism, 2022)
Objective: The goal of this study was to determine the glucometabolic effects of acute activation of Gs signaling in skeletal muscle (SKM) in vivo and its contribution to whole-body glucose homeostasis. Methods: To address this question, we studied mice that express a Gs-coupled designer G protein-coupled receptor (Gs-DREADD or GsD) selectively in skeletal muscle. We also identified two Gs-coupled GPCRs that are endogenously expressed by SKM at relatively high levels (β2-adrenergic receptor and CRF2 receptor) and studied the acute metabolic effects of activating these receptors in vivo by highly selective agonists (clenbuterol and urocortin 2 (UCN2), respectively). Results: Acute stimulation of GsD signaling in SKM impaired glucose tolerance in lean and obese mice by decreasing glucose uptake selectively into SKM. The acute metabolic effects following agonist activation of β2-adrenergic and, potentially, CRF2 receptors appear primarily mediated by altered insulin release. Clenbuterol injection improved glucose tolerance by increasing insulin secretion in lean mice. In SKM, clenbuterol stimulated glycogen breakdown. UCN2 injection resulted in decreased glucose tolerance associated with lower plasma insulin levels. The acute metabolic effects of UCN2 were not mediated by SKM Gs signaling. Conclusions: Selective activation of Gs signaling in SKM causes an acute increase in blood glucose levels. However, acute in vivo stimulation of endogenous Gs-coupled receptors enriched in SKM has only a limited impact on whole-body glucose homeostasis, most likely due to the fact that these receptors are also expressed by pancreatic islets where they modulate insulin release.